A cyclic vicinal bis(tetraketone) and structural investigations of formoins - Peter, Matthias; Gleiter, Rolf; Rominger, Frank; Oeser, Thomas (European journal of organic chemistry, 2004)
Investigations of simple formoins such as 2,5-bis(1,1-dimethyl-2-phenylethyl)-2,4-dihydroxyfuran-3(2H)-one (17), benzoylformoin (18), p-toluoylformoin (19), pivaloylformoin (20), and the 2,4-dihydroxy-2,5-bis(heterocycl-2-yl)furan-3-ones 21−23 (heterocycle = furan, thiophene, selenophene) by NMR spectroscopy in DMSO showed the dihydroxyfuranone skeleton and not an enediol structure. The formoin 17 was oxidized to the corresponding tetraketone 10. The intermolecular double benzoin condensation of 1,4-bis(2,2dimethyl-3,4-dioxobutyl)benzene (27) affords, in low yield, the bis(formoin) 29, and this could be oxidized to provide 2,2,2′,2′,7,7,7′,7′-octamethyl[8.8]paracyclophan-3,3′,4,4′5,5′6,6′-octaone (9). The molecular structures of 17 and 29, the monohydrate of 10 (30), and also the dihydrate of 9 (31) are reported. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)
Gesehen am 27.10.2020